2012
DOI: 10.1007/jhep07(2012)088
|View full text |Cite
|
Sign up to set email alerts
|

Holographic entanglement entropy in insulator/superconductor transition

Abstract: We investigate the behaviors of entanglement entropy in the holographical insulator/superconductor phase transition. We calculate the holographic entanglement entropy for two kinds of geometry configurations in a completely back-reacted gravitational background describing the insulator/superconductor phase transition. The non-monotonic behavior of the entanglement entropy is found in this system. In the belt geometry case, there exist four phases characterized by the chemical potential and belt width.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 60 publications
5
72
0
1
Order By: Relevance
“…More recently, Kuang et al examined the properties of the entanglement entropy in the four-dimensional AdS black hole and found that near the contact interface of the superconducting to normal phase the entanglement entropy has a different behavior due to the proximity effect [50]. In the insulator/superconductor transition, it is shown that the entanglement entropy for a half space first increases and reaches its maximum at a certain chemical potential and then decreases monotonically as chemical potential increases [51][52][53][54]. As a further step along this line, it is of great interest to generalize the investigation on the entanglement entropy of general holographic superconductors via the Stückelberg mechanism and study systematically the effects of the mass, model parameter and backreaction on the entropy.…”
Section: Jhep06(2014)011mentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Kuang et al examined the properties of the entanglement entropy in the four-dimensional AdS black hole and found that near the contact interface of the superconducting to normal phase the entanglement entropy has a different behavior due to the proximity effect [50]. In the insulator/superconductor transition, it is shown that the entanglement entropy for a half space first increases and reaches its maximum at a certain chemical potential and then decreases monotonically as chemical potential increases [51][52][53][54]. As a further step along this line, it is of great interest to generalize the investigation on the entanglement entropy of general holographic superconductors via the Stückelberg mechanism and study systematically the effects of the mass, model parameter and backreaction on the entropy.…”
Section: Jhep06(2014)011mentioning
confidence: 99%
“…Applying the Stückelberg mechanism to insulator/superconductor phase transition in the five-dimensional AdS soliton spacetime, it stated in [52] that the entanglement entropy serves as a good probe to the order of phase transition. We will generalize the discussion in [51,52,54] to the more general superconductor by choosing various masses m and charges q of the scalar field, and examining the formation of scalar hair in another Stückelberg superconductor model which is different from that in ref. [52].…”
Section: Bulk Equations Of Motion and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus entanglement entropy can be used as a diagnostic for QPT. Behavior of entanglement entropy near various holographic thermal phase transitions were investigated before in [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, starting with [11], there have been several studies of the change of behavior of the entanglement entropy in holographic models of critical phase transitions. [11] examined a model of s-wave holographic superconducting transition, [12] considered a model of an insulator-superfluid transition while [13] studies a model of holographic p-wave superconductor phase transition based on [14,15]. Recently, [16,17] extended the study of the holographic entanglement entropy near critical phase transitions.…”
Section: Introductionmentioning
confidence: 99%